An Autonomous Log Storage Management Protocol with Blockchain Mechanism and Access Control for the Internet of Things - Hsu, Chien-Lung (Sensors (Basel), 2020)
As the Internet of Things (IoT) has become prevalent, a massive number of logs produced by IoT devices are transmitted and processed every day. The logs should contain important contents and private information. Moreover, these logs may be used as evidences for forensic investigations when cyber security incidents occur. However, evidence legality and internal security issues in existing works were not properly addressed. This paper proposes an autonomous log storage management protocol with blockchain mechanism and access control for the IoT. Autonomous model allows sensors to encrypt their logs before sending it to gateway and server, so that the logs are not revealed to the public during communication process. Along with blockchain, we introduce the concept “signature chain”. The integration of blockchain and signature chain provides efficient management functions with valuable security properties for the logs, including robust identity verification, data integrity, non-repudiation, data tamper resistance, and the legality. Our work also employs attribute-based encryption to achieve fine-grained access control and data confidentiality. The results of security analysis using AVSIPA toolset, GNY logic and semantic proof indicate that the proposed protocol meets various security requirements. Providing good performance with elliptic curve small key size, short BLS signature, efficient signcryption method, and single sign-on solution, our work is suitable for the IoT.